The IMF and its critics : reform of global financial architecture - Gilbert, C. L.; Vines, David (Global economic institutions., 2004)
Leading economists argue that the IMF should be better equipped for solving international financial crises. Combining rigorous economic analysis with insider perspectives on current policy debates surrounding the future of the IMF, this book is essential for anyone interested in the role of international financial institutions in our globalised economy.